Peningkatatn Kesadaran Masyarakat Di Kelurahan Bener Tegalrejo Yogyakarta Terhadap Bahaya Pernikahan Di Bawah Umur Melalui Penyuluhan Hukum - Hapsari, Murti Ayu (Universitas Negeri Gorontalo, 2021)
Underage marriage is something that still happens a lot in society, there are many negative impacts that arise due to underage marriage, ranging from the possibility of violence in the household to the potential for maternal and child deaths that occur too early. Marriage is ideally carried out by a partner who is physical and can be said to be an adult, thus being able to be responsible for himself and for others. Prevention of underage marriages is also closely related to the fulfillment of children's rights which should be fulfilled but their access is closed because they are considered adults and have to take care of their own household. To this problem finally issued a revision of Law No. 1 of 1974 related to the minimum marriage limit for children especially women, who were originally 16 years old to 19 years old as a form of responsibility to protect their citizens. Based on the survey results from the Janabadra University Community Service Team, village officials view this issue as one of the important issues that must be submitted by the community, the request was followed up with legal counseling related to Law no. 16 of 2019 in conjunction with Law No. 1 of 1974. The preparation stage was coordinated with the Janabadra University Community Service Team to determine the time and place, then continued with preparations to look for materials and materials to be delivered to the fish. The implementation of the activities carried out with the presentation of the material followed by a question and answer session with the counseling participants.